2022
DOI: 10.1002/mrm.29236
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of undersampling parameters for 3D intracranial compressed sensing MR angiography at 7 T

Abstract: Purpose: 3D time-of-flight MRA can accurately visualize the intracranial vasculature but is limited by long acquisition times. Compressed sensing reconstruction can be used to substantially accelerate acquisitions. The quality of those reconstructions depends on the undersampling patterns used. In this work, we optimize sets of undersampling parameters for various acceleration factors of Cartesian 3D time-of-flight MRA. Methods: Fully sampled datasets, acquired at 7 Tesla, were retrospectively undersampled usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Maximum intensity projection (MIP) images were generated from the source images of the TOF MRA. As previous work reported that the vessel‐masked structural similarity index measure (SSIM) well correlates with visual assessment by radiologists when evaluating the reconstructions from retrospectively undersampled TOF MRA dataset, 13 , 34 we adopted the vessel‐masked SSIM in addition to a standard SSIM in this study to assess the accuracy of the reconstruction from retrospectively undersampling. Additionally, CBR, SSIM, and vessel‐masked SSIM metrics were compared between different accelerated sampling schemes using a two‐tailed paired t test with Bonferroni correction, and adjusted P values less than 0.05 were considered statistically significant ( N = 6).…”
Section: Methodsmentioning
confidence: 99%
“…Maximum intensity projection (MIP) images were generated from the source images of the TOF MRA. As previous work reported that the vessel‐masked structural similarity index measure (SSIM) well correlates with visual assessment by radiologists when evaluating the reconstructions from retrospectively undersampled TOF MRA dataset, 13 , 34 we adopted the vessel‐masked SSIM in addition to a standard SSIM in this study to assess the accuracy of the reconstruction from retrospectively undersampling. Additionally, CBR, SSIM, and vessel‐masked SSIM metrics were compared between different accelerated sampling schemes using a two‐tailed paired t test with Bonferroni correction, and adjusted P values less than 0.05 were considered statistically significant ( N = 6).…”
Section: Methodsmentioning
confidence: 99%
“…An acceleration factor larger than seven has been achieved on 7 T TOF‐MRA, 36 enabling a 0.3 mm isotropic acquisition covering the whole LSAs in less than 8 minutes 36 . The image quality may be further improved by the appropriate choice of under‐sampling parameters 41 …”
Section: Time‐of‐flight Mr Angiographymentioning
confidence: 99%
“…36 The image quality may be further improved by the appropriate choice of undersampling parameters. 41 TOF-MRA is mainly used to analyze the anatomical structures of cerebral arteries. The diameters and degree of stenosis can be measured on TOF-MRA.…”
Section: Time-of-flight Mr Angiographymentioning
confidence: 99%
“…CS was first introduced for 1 H MRI, but CS validity has also been investigated with non‐proton MRI such as helium‐3, 11 fluorine‐19, 12 carbon‐13, 13 sodium‐23, 14 and xenon‐129 15,16 . Although these studies showed good agreement between fully and undersampled images, the quality of images reconstructed by CS depends strongly on multiple factors and has several drawbacks: (1) sparse transformations can be insufficient for representing complex image components and result in artifacts, particularly in medical imaging; (2) CS employs iterative procedures, which are costly and often result in oversmoothed images; (3) hyperparameters such as updating rates, weighting factors, and so on must be selected manually, which takes time and can differ depending on the patient and anatomy being assessed 17 . To our knowledge, there is no conclusive information about the effect of suboptimal sampling patterns for CS HP 129 Xe lung MRI 18 .…”
Section: Introductionmentioning
confidence: 99%